Small-Molecule Probes Targeting the Viral PPxY-Host Nedd4 Interface Block Egress of a Broad Range of RNA Viruses - Han, Ziying; Lu, Jianhong; Liu, Yuliang; Davis, Benjamin; Lee, Michael S.; Olson, Mark A.; Ruthel, Gordon; Freedman, Bruce D.; Schnell, Matthias J.; Wrobel, Jay E.; Reitz, Allen B.; Harty, Ronald N. (Journal of virology, 2014)
Budding of filoviruses, arenaviruses, and rhabdoviruses is facilitated by subversion of host proteins, such as Nedd4 E3 ubiquitin ligase, by viral PPxY late (L) budding domains expressed within the matrix proteins of these RNA viruses. As L domains are important for budding and are highly conserved in a wide array of RNA viruses, they represent potential broad-spectrum targets for the development of antiviral drugs. To identify potential competitive blockers, we used the known Nedd4 WW domain-PPxY interaction interface as the basis of an in silico screen. Using PPxY-dependent budding of Marburg (MARV) VP40 virus-like particles (VLPs) as our model system, we identified small-molecule hit 1 that inhibited Nedd4-PPxY interaction and PPxY-dependent budding. This lead candidate was subsequently improved with additional structure-activity relationship (SAR) analog testing which enhanced antibudding activity into the nanomolar range. Current lead compounds 4 and 5 exhibit on-target effects by specifically blocking the MARV VP40 PPxY-host Nedd4 interaction and subsequent PPxY-dependent egress of MARV VP40 VLPs. In addition, lead compounds 4 and 5 exhibited antibudding activity against Ebola and Lassa fever VLPs, as well as vesicular stomatitis and rabies viruses (VSV and RABV, respectively). These data provide target validation and suggest that inhibition of the PPxY-Nedd4 interaction can serve as the basis for the development of a novel class of broad-spectrum, host-oriented antivirals targeting viruses that depend on a functional PPxY L domain for efficient egress. IMPORTANCE There is an urgent and unmet need for the development of safe and effective therapeutics against biodefense and high-priority pathogens, including filoviruses (Ebola and Marburg) and arenaviruses (e.g., Lassa and Junin) which cause severe hemorrhagic fever syndromes with high mortality rates. We along with others have established that efficient budding of filoviruses, arenaviruses, and other viruses is critically dependent on the subversion of host proteins. As disruption of virus budding would prevent virus dissemination, identification of small-molecule compounds that block these critical viral-host interactions should effectively block disease progression and transmission. Our findings provide validation for targeting these virus-host interactions as we have identified lead inhibitors with broad-spectrum antiviral activity. In addition, such inhibitors might prove useful for newly emerging RNA viruses for which no therapeutics would be available.